PERANCANGAN CERITA BERGAMBAR PERMAINAN TRADISIONAL MINANGKABAU CAK BUR - DIKI HERDIAN, Drs. Syafwan, M.Si. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of designing the tradisional Minangkabau Cak Bur picture game is to promote the Cak Bur game to children to be motivated to get to know, play tha game and love the game. Picture stories can not only be obtained through books, but now can be through digital media.Glass Box method is a method that thinks logically and rationally used in the design of tradisional Minangkabau Cak Bur picture games. Pictorial story theory, media, new media, books, visual communication designs, illustrations, layouts, colors, typography and childrens phychology are included in the theory in the design of picture stories in Cak Bur games. By using SWOT analysis to obtain data obtained in the design of picture stories.Digital based picture story design as the main media is also accompanied by supporting media to draw peoples attention to the process of launching picture stories, such as books, posters, x-banners, t-shirt, totebags and stickers.Keywords : games, tradisional, stories, media